Digitization and Digitalization in the MSME Sector Success Stories and Challenges from Emergent Countries, with Examples from Some Asian Countries and Uganda. - Sazir Nsubuga Mayanja (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
ASEAN Member States (AMS) have a Policy Guideline on Digitalisation of ASEAN Micro Enterprises. It was compiled through an inclusive, multi-stakeholder process with support from the ASEAN Secretariat, known as the ASEAN Coordinating Committee on Micro, Small and Medium Enterprises (ACCMSME). The Organisation for Economic Development and Cooperation (OECD) as well as representatives of the private sector in ASEAN participated. In 2020, at the 37th summit of the ASEAN countries, the ASEAN Comprehensive Recovery Framework (ACRF) was adopted. Initiatives arising from these kinds of regional efforts have led to impressive achievements. As a result, Industry statistics estimate that the ASEAN region’s internet economy will exceed a gross market value of US240b by 2025, more than twice that of US72b in 2018. The ASEAN population is the most engaged mobile Internet users in the world. On the other hand, partly because of the convergence of low scores on the digital and entrepreneurship systems, Africa is precariously positioned on the Global Entrepreneurship Index Rank, the UNCTAD E-commerce Index Rank, and the Availability of venture capital scores. To succeed, the region has deliberately and seriously developed plans and programs, all along involving governments, global partners like OECD, and the private sector. The nodules in the network create a linkage that enhances accountability and responsibility such that none slackens in their efforts. The findings of this study, which has adopted exploratory research techniques, are that, first digitalization is no longer an option, but a necessity for economies and their MSMEs. Secondly, that well-developed infrastructure by way of broadband penetration by itself is not sufficient.